Arranging Orchestral Music on an Early Nineteenth-Century French Piano - Montebugnoli, Luca (2024)
Arranging Orchestral Music on an Early Nineteenth-century French Piano
Erasmus+
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850